2011
DOI: 10.1248/bpb.34.272
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Induced Toxicity in Rats: Blood Serum Chemistry, Antioxidative Enzymes in Red Blood Cells and Histopathological Studies

Abstract: Lithium is commonly used in treating mental disorders and bipolar diseases. As physicians frequently keep the patients on long-term lithium therapy, awareness of the numerous side effects and pathogenesis of this lightest alkali metal is needed for such treatments. The present study was designed to evaluate the toxic effect of small doses of lithium chloride in male Wistar rats. The oral administration of lithium chloride (15, 30 mg/kg body wt) for 7 weeks through their drinking water elicited a significant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 38 publications
6
19
0
6
Order By: Relevance
“…The principle of the test was based on the method described by Peake and Whiting (2006). Reflotron, is a solid phase reagent technology capable of measuring a wide range of analytes on whole blood, plasma or serum samples and the results show good concordance with conventional wet chemistry methods (Ahmad et al, 2011).…”
Section: Serum Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…The principle of the test was based on the method described by Peake and Whiting (2006). Reflotron, is a solid phase reagent technology capable of measuring a wide range of analytes on whole blood, plasma or serum samples and the results show good concordance with conventional wet chemistry methods (Ahmad et al, 2011).…”
Section: Serum Analysismentioning
confidence: 86%
“…Histopathology: This was done according to the standard procedure (Ahmad et al, 2011). In brief, after blood collection, the mice were sacrificed by cervical dislocation.…”
Section: Serum Analysismentioning
confidence: 99%
“…ATPase, hepatic phase II drug metabolizing enzymes and hepatic trace elemental profile (Tandon et al 1997(Tandon et al , 1999. Lithium stimulates transamination reaction in hepatic and renal tissues and inhibits the levels of serum alanine and aspartate transaminases (ALT and AST) (Ahmad et al 2011). Lithium reduced the glutathione (GSH) levels and also increased lipid peroxidation and the activities of antioxidative enzymes, which included catalase, glutathione S-transferase, and superoxide dismutase (Malhotra and Dhawan 2008).…”
Section: Introductionmentioning
confidence: 99%
“…But all histopathological changes were more prominent at higher dose. Ahmad et al [26] reported that LiCl treatment caused significant and dose-dependent tissue damages in the liver and kidney. The results of our study are consistent with their findings as far as histopathological changes are concerned.…”
Section: Discussionmentioning
confidence: 99%